AB0241 What proportion of ra patients are truly in remission? a survey of rheumatologists of the auvergne region of france. (12th June 2018) - Dubost, J.J.; Pereira, B.; Fan, A.; Meyer, D.; Verrière, D.; Melac-Ducamp, S.; Glace, B.; Demarquilly, F.; Gendey, M.; Maillet, B.; Zbadi, K.; Voquer, C.; et al.
Abstract : Background: The treatment of rheumatoid arthritis (RA) is aimed to achieve remission. Objectives: To determine the proportion of RA patients in remission among the population treated by rheumatologists in Auvergne, France. Methods: A 3 month survey involving 24 rheumatologists, not practicing at university hospitals, from the Auvergne region of France. The rheumatologists completed records on each RA patient detailing the parameters of RA activity (tender joint count, swollen joint count, pain VAS, patient's assessed activity VAS, physician's assessed activity VAS, ESR and CRP), as well as the RA treatment administered, and if this treatment was modified. Results: Overall, 15 rheumatologists provided 455 records. These comprised 330 women (74%) and 125 men, aged on average 64.8 years old ±12.6. The patients had suffered from RA for 7 years on average, 4–14 77.3% were positive for rheumatoid factor, and 76.2% for anti-CCP. They underwent the following treatments: NSAIDs (19%), corticoids (24.4%; 5 mg 4–6 ), methotrexate (80.4%; 15 mg; 10–15 leflunomide (4.4 %), hydroxychloroquine (11%), sulfasalazine (2.4%), anti-TNF (21.9%), other biotherapy (8.8%), no DMARD (3.1%), ≥2 DMARDs (31.8%). The proportion of patients in remission varied depending on different definitions as follows: DAS28-ESR≤2.6: 61.5% (low activity: 79%); DAS28-CRP≤2.4: 59.5%, DAS 28-CRP≤2.1: 47.2%; SDAI ≤3.3: 40.1% (low activity: 80%); CDAI ≤2.8: 36.0% (low activity: 81.5%); ACR/EULAR: 31.8%; simplified ACR/EULAR: 39.1%; physician-assessed remission (VAS≤1): 52.3%; patient-assessed remission (VAS≤1): 47.3%. There was moderate to good correlation between the ACR/EULAR and SDAI criteria (κ=0.70) and CDAI criteria (κ=0.72), while there was weak correlation between ACR/EULAR and DAS 28-ESR (κ=0.45). The physicians' and patients' assessments did not correlate well with the remission criteria. Compared to those who were not in remission, the patients assessed as being in remission according to DAS28-ESR and ACR/EULAR criteria were younger, had been treated with less corticoids, had more frequently received anti-TNF, and had less frequently had their treatment modified. Conclusions: Our findings were reassuring, with 32% (ACR/EULAR) to 62% (DAS) of RA patients followed up by rheumatologists outside of university hospitals assessed as being in remission, and 80% presenting with low disease activity. A total of 97% received DMARD, 30% received biotherapy, and a quarter corticoids. We found moderate to good correlation between ACR/EULAR and SDAI and CDAI; whereas there was low correlation between ACR/EULAR and DAS 28-ESR. The physicians' and patients' assessments did not correlate well with the remission criteria. Disclosure of Interest: None declared